U.S. worldwide taxation and domestic mergers and acquisitions - Harris, Jeremiah; O'Brien, William (Journal of Accounting and Economics, 2018)
This study shows that domestic mergers and acquisitions (M&A) were inhibited by the U.S.’s worldwide tax policy on foreign-earned income. Double Irish structures, a complex web of subsidiaries that reduce foreign tax rates and therefore increase potential repatriation tax rates, are associated with lower levels of domestic M&A by U.S. firms. These results do not reflect a continuation of prior trends or declines in worldwide acquisitiveness and are robust to several econometric approaches. We suggest that the Double Irish variable mitigates a confounding effect in an alternative tax variable that clouds inferences in tests of repatriation taxes and domestic M&A.